2018
DOI: 10.1242/jcs.216267
|View full text |Cite
|
Sign up to set email alerts
|

Common signalling pathways in macrophage and osteoclast multinucleation

Abstract: Macrophage cell fusion and multinucleation are fundamental processes in the formation of multinucleated giant cells (MGCs) in chronic inflammatory disease and osteoclasts in the regulation of bone mass. However, this basic cell phenomenon is poorly understood despite its pathophysiological relevance. Granulomas containing multinucleated giant cells are seen in a wide variety of complex inflammatory disorders, as well as in infectious diseases. Dysregulation of osteoclastic bone resorption underlies the pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
167
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(173 citation statements)
references
References 158 publications
(177 reference statements)
5
167
0
1
Order By: Relevance
“…That thesis is supported by the recent research performed by Rao et al [10] who discovered that downregulation of pro-inflammatory cytokines prevents inflammation induced osteoporosis. Also, macrophages directly participate in the formation and activation of osteoclasts [11]. On the other hand, maintaining physiological activity of macrophages is necessary to bone formation, since it was shown, that macrophages depletion in mice resulted in 25% reduction of bone mineral density and a 70% reduction in the number of trabecular bone compared to control littermates [12].…”
Section: Introductionmentioning
confidence: 99%
“…That thesis is supported by the recent research performed by Rao et al [10] who discovered that downregulation of pro-inflammatory cytokines prevents inflammation induced osteoporosis. Also, macrophages directly participate in the formation and activation of osteoclasts [11]. On the other hand, maintaining physiological activity of macrophages is necessary to bone formation, since it was shown, that macrophages depletion in mice resulted in 25% reduction of bone mineral density and a 70% reduction in the number of trabecular bone compared to control littermates [12].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have shown that following a TB mycobacterial infection of the lung, macrophages are recruited to the infection site and become reprogrammed to "seal off" the infected cells; they do this by flattening and assembling E-cadherin-rich interdigitations with one another to form an epitheliod "wall" (Pagán and Ramakrishnan, 2018). Granulomas can also trigger not just adhesion but fusion of macrophages to generate giant multinucleate cells, sometimes called foreign body giant cells (FBGCs), with obvious parallels to multinucleated, bone-dissolving osteoclasts, also from the myeloid cell lineage (Pereira et al, 2018). Metchnikoff's student Tchistowitch "witnessed all the transition stages between mononuclear leukocytes…through to giant cells in the pulmonary alveoli of rabbits" (Metchnikoff, 1968).…”
Section: Encapsulation and Cell-cell Fusionmentioning
confidence: 99%
“…32 Macrophages are predominant cells in articular joints of RA patients and intercellular adhesion molecule-1 (ICAM-1) promotes macrophage polarization (a measure of macrophage activation). 32 Macrophages are predominant cells in articular joints of RA patients and intercellular adhesion molecule-1 (ICAM-1) promotes macrophage polarization (a measure of macrophage activation).…”
Section: C-fhhdm-1 Inhibits Osteoclast Formation and Macrophage Actmentioning
confidence: 99%